استخدام التحليل العاملي لدراسة المتغيرات المؤثرة في التعاملات بالبيع الآجل (المجلة العراقية للعلوم الاقتصادية, 2018)
saling by credit considered a phenomena known in the daily dealing and it is one of the policies pursued by some companies in their dealing with customers, that way has increased recently. Accordingly ,this research was made to study the factors affecting dealing by credit. Data were obtained through a search form distributed asample of traders to know their point of view and then that data saved on the statistic program (spss) then it was treated by using factorial analysis of the principal components way therefore, the results, conclusion and recommendations have been reached in the research.